Efficacy and Safety of Pharmacotherapy of Chronic Gastritis: Khasiat dan Keamanan Farmakoterapi Gastritis Kronis - Ochilova Gulrukh Saidovna; Ochilov Alisher Kamilovich (Academia Open, 2022)
The MDR-1 gene encodes P-glycoprotein, a vital membrane protein found in various normal cells throughout the body. This protein plays a crucial role in actively facilitating the absorption of drugs across cell membranes. Understanding the expression of P-glycoprotein is essential for comprehending drug pharmacokinetics and optimizing pharmacotherapy outcomes. In this study, our goal was to investigate the influence of P-glycoprotein expression on drug permeability and its implications for therapeutic effectiveness. Through a comprehensive analysis of existing literature, we explored the methods employed to assess P-glycoprotein activity and its impact on drug absorption. The results unveiled the pivotal role of P-glycoprotein in modulating drug permeability and highlighted its significance in determining pharmacotherapy outcomes. This research emphasizes the necessity of considering P-glycoprotein expression when designing drug delivery strategies, enabling targeted therapies, and maximizing therapeutic efficacy. Highlights: P-glycoprotein: Key regulator of drug permeability and cellular absorption. Influence of P-glycoprotein expression on pharmacotherapy outcomes. Importance of considering P-glycoprotein in drug delivery and targeted therapies. Keywords: MDR-1 gene, P-glycoprotein, drug permeability, pharmacokinetics, pharmacotherapy effectiveness.